Räumliche und zeitliche Funktionen von Berührungen als multimodale Ressource in der Physiotherapie vor und nach COVID-19 - Ortner, Heike; Wopfner, Lena (Linguistik Online, 2026)
Physiotherapy is an interactive production of therapists and patients, whereby touch is probably the most important multimodal resource. This article focuses on the aspect of negotiation and representation of space and time regarding the interactional resource of touch in physiotherapy. The analysis highlights the complex role of touch as a multimodal resource that combines spatial orientation, temporal sequencing, and embodied communication in therapeutic settings. Spatial affordances and arrangements, such as proximity and body orientation, are essential for enabling therapeutic touch, which conveys critical information about movement and patient support. Temporal sequencing, meanwhile, structures the coordination of gestures, speech, and touch, facilitating the patient’s engagement in movement tasks. The examples from the video data demonstrate how the physiotherapeutic interactions before and after COVID-19 build on robust practices of touch, while the retrospective interviews reflect on the interactional consequences of physical distancing adaptations during the pandemic.